Analysis of parental decisions to use orthokeratology for myopia control in successful wearers. (16th October 2020) - Wang, Xingyu; Yang, Bi; Liu, Longqian; Cho, Pauline
Abstract: Purpose: To investigate factors that influence parental decisions to use orthokeratology (ortho‐k) as a myopia control method for their children, and parents' perspectives during children's ortho‐k treatment in a hospital setting. Methods: Parents/guardians of children wearing ortho‐k lenses for at least six months were required to complete a face‐to‐face survey to investigate the reasons for choosing ortho‐k and their experience of the treatment. Results: Parents/guardians of 128 ortho‐k wearers were recruited from the West China Hospital, Sichuan, China. The majority of the participants (74%) were mothers. Wearers' mean age at the time of the survey was 12.0 ± 2.0 years, with a mean history of ortho‐k lens wear of 20.3 ± 8.0 months. Most participants had learned about ortho‐k through word of mouth (56%) or from ophthalmologists (40%); in China, only ophthalmologists may prescribe ortho‐k. The highest ranked motivation was the rapid progression of their children's myopia (54%), followed by ophthalmologists' advice (17%) or participants' who felt they had obtained enough knowledge (17%) of ortho‐k (Kruskal‐Wallis test, p  = 0.002). 'Effectiveness' was the most common reason that participants decided to use ortho‐k (81%), and potential injury was their major concern (75%). Itchy/sore eye was the most common initial adverse effect experienced with lens wear (22%), while a lost or broken ortho‐k lens was the most frequently reported problem (34%). Parents of older lens wearers were significantly less involved in all procedures (Spearman rank correlation test, all p  < 0.001). Most wearers, according to either the participants or the wearers themselves, were willing to wear ortho‐k lenses at treatment commencement (80%), and the most common reason was 'to avoid having to wear spectacles in the daytime'. Conclusions: The most powerful motivation for parents to enrol their children in ortho‐k treatment was the rapid progression of myopia. The main reason why participants chose ortho‐k, which most participants learned of by word of mouth, was the effectiveness of the treatment. During use, the most common symptom reported was itchy or sore eyes, but only initially. Children's willingness to participate is very important for successful ortho‐k treatment; however, their motivation can be quite different from that of their parents. Ortho‐k is a well‐accepted option for myopia control in children.